The politics of writing studies : reinventing our universities from below - Samuels, Robert, 1961- (Utah State University Press, 2017)
"Drawing from pivotal texts in the field of writing studies, The Politics of Writing Studies shows how the use and abuse of contingent faculty at institutions of higher education affect the efficacy and perceived status of composition programs at universities and colleges in the United States"--Provided by publisher